A Mechanization of the Blakers-Massey Connectivity Theorem in Homotopy Type Theory - Hou (Favonia), Kuen-Bang; Finster, Eric; Licata, Daniel R.; Lumsdaine, Peter LeFanu (LICS 2016 : proceedings of the 31st annual ACM-IEEE Symposium on Logic in Computer Science : July 5-8, 2016, New York City, USA, 2016)
This paper contributes to recent investigations of the use of homotopy type theory to give machine-checked proofs of constructions from homotopy theory. We present a mechanized proof of a result called the Blakers-Massey connectivity theorem, which relates the higher-dimensional loop structures of two spaces sharing a common part (represented by a pushout type, which is a generalization of a disjoint sum type) to those of the common part itself. This theorem gives important information about the pushout type, and has a number of useful corollaries, including the Freudenthal suspension theorem, which was used in previous formalizations. The proof is more direct than existing ones that apply in general category-theoretic settings for homotopy theory, and its mechanization is concise and high-level, due to novel combinations of ideas from homotopy theory and from type theory.